Production of medicinally important secondary metabolites (stigmasterol and hecogenin) from root cultures of Chlorophytum borivilianum (Safed musli) - Bathoju, Gayathri; Giri, Archana (Recent Research in Science and Technology, 2012)
Chlorophytum borivilianum (Liliaceae) commonly known as safed musli is a perennial rhizomatous herb widely distributed in the pan tropical regions containing pharmaceutically important saponins. Root cultures were established from micropropagated plants of Chlorophytum borivilianum on Murashige and Skoog media supplemented with 3 mg/l Indole Butyric Acid. Growth kinetics of roots was done under shake flask conditions and maximum biomass was observed after 4 weeks of culture. A twenty four-fold increase of fresh biomass was evident in shake cultures. These in vitro propagated roots were tested for the production of pharmaceutically important secondary metabolites stigmasterol and hecogenin. A maximum of 46.4 mg/gDCW of stigmasterol and 685 mg/gDCW of hecogenin was evident in these cultures.